Impact of enterococcal colonization and infection in solid organ transplantation recipients from the Swiss Transplant Cohort Study. Issue 1 (16th December 2013) - Bucheli, E.; Kralidis, G.; Boggian, K.; Cusini, A.; Garzoni, C.; Manuel, O.; Meylan, P.R.A.; Mueller, N.J.; Khanna, N.; van, C.; Berger, C.; Koller, M.T.; et al.
Abstract Background The burden of enterococcal infections has increased over the last decades with vancomycin‐resistant enterococci (VRE) being a major health problem. Solid organ transplantation is considered as a risk factor. However, little is known about the relevance of enterococci in solid organ transplantation recipients in areas with a low VRE prevalence. Methods We examined the epidemiology of enterococcal events in patients followed in the Swiss Transplant Cohort Study between May 2008 and September 2011 and analyzed risk factors for infection, aminopenicillin resistance, treatment, and outcome. Results Of the 1234 patients, 255 (20.7%) suffered from 392 enterococcal events (185 [47.2%] infections, 205 [52.3%] colonizations, and 2 events with missing clinical information). Only 2 isolates were VRE. The highest infection rates were found early after liver transplantation (0.24/person‐year) consisting in 58.6% of Enterococcus faecium. The highest colonization rates were documented in lung transplant recipients (0.33/person‐year), with 46.5% E. faecium. Age, prophylaxis with a betalactam antibiotic, and liver transplantation were significantly associated with infection. Previous antibiotic treatment, intensive care unit stay, and lung transplantation were associated with aminopenicillin resistance. Only 4/205 (2%) colonization events led to an infection. Adequate treatment did not affect microbiological clearance rates. Overall mortality was 8%; no deaths were attributable to enterococcal events. Conclusions Enterococcal colonizations and infections are frequent in transplant recipients. Progression from colonization to infection is rare. Therefore, antibiotic treatment should be used restrictively in colonization. No increased mortality because of enterococcal infection was noted.